A Clinical Audit on Appropriateness of Intravenous Fluid Prescribing Practices in Hospitalized Adult Inpatients: Evaluating Compliance with National Guidelines - ULLAH, NAQEEB; UMAR, ZEESHAN; SHAH, SYED HUSSAINI; SHAH, SYED HASSNAIN; ALI, WAJID; MUKHTIAR, SANA; NAWAZ, SAJID; Nazir, Tamanna; HANFI, HANIF ULLAH; IQBAL, SHEEMA; AHMAD, ZUBAIR (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Intravenous (IV) fluid therapy is a routine yet critical aspect of inpatient care, essential for maintaining fluid and electrolyte balance. However, inappropriate prescribing can result in significant morbidity. Aim: To assess appropriateness of IV fluid prescribing practices among adult inpatients at Lady Reading Hospital, Peshawar & evaluate compliance with NICE CG174 guidelines. Methods: A retrospective audit was conducted over six months (January–June 2024). Data were collected from 200 randomly selected patient records across general medicine, surgery, and orthopedics departments. A structured tool based on NICE guidelines was used to evaluate key parameters such as initial fluid assessment, documentation, reassessment, and fluid type. Data were analyzed using SPSS version 25. Results: Only 48% of IV fluid prescriptions were fully compliant with NICE guidelines; 35% were partially compliant, and 17% were non-compliant. Documentation of initial assessment occurred in 70% of cases, while ongoing reassessment was documented in just 49%. General Medicine showed the highest compliance (55%), and Orthopedics the lowest (38%). Normal Saline was the most frequently prescribed fluid (65%). Conclusion: The audit reveals suboptimal adherence to national guidelines, with notable interdepartmental variation. Targeted interventions, including staff training and standardized protocols, are recommended to enhance safe and effective fluid prescribing practices.